Method and device for measuring fracture toughness of brittle material based on laser thermally induced crack propagation

Through the laser thermal crack propagation method, a laser is used to inject energy into the crack ends of the ceramic material, and combined with the thermal imager and Griffith energy release theory, the fracture toughness of the ceramic material is quickly and accurately measured, solving the problems of time-consuming and labor-intensive experiments and high data dispersion in the prior art.

CN119595691AActive Publication Date: 2025-03-11XI AN JIAOTONG UNIV +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411743964.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-11
Estimated Expiration
2044-11-30

AI Technical Summary

Technical Problem

The prior art uses time and effort to measure the fracture toughness of ceramic materials, and the data is highly dispersible, making it difficult to achieve fast and accurate measurements.

Method used

Using a laser-based thermal crack propagation method, energy is injected into the crack end of the ceramic material through a laser, temperature changes are read using a thermal imager, and combined with the Griffith energy release theory, the energy release rate and fracture toughness of the material are calculated.

Benefits of technology

This method simplifies the experimental process, is simple in equipment and easy to operate, can quickly and accurately measure the fracture toughness of ceramic materials, and has strong reliability in the results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595691A_ABST
    Figure CN119595691A_ABST
Patent Text Reader

Abstract

The invention relates to a method and a device for measuring fracture toughness of a brittle material based on laser thermally induced crack propagation. The method comprises the following steps: firstly, prefabricating a crack on a brittle material thin plate; then adjusting the temperature power of a laser, and adjusting a laser action point to a position 1.5 mm behind the tip of the crack on the tested sample for irradiation; measuring the length of the crack after expansion, and calculating the crack area by combining with the material thickness; the laser action time and the laser input power are recorded, the laser action energy is calculated, and the energy for crack propagation is calculated through theoretical derivation combination and simulation analysis; and calculating the energy release rate and fracture toughness of the material according to the crack area and energy. The measuring device is simple and easy and convenient to operate, the depended formula is widely accepted in the industry, the universality is good, and the reliability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of experimental testing, and in particular relates to a method and a device for measuring the fracture toughness of ceramic materials based on laser thermal crack extension. Background Art

[0002] Ceramic materials are mainly composed of oxides, carbides, nitrides, halogen compounds, borides, silicates, aluminates, phosphates, borates and other substances of certain elements. Typical common ceramic materials are sintered from natural raw materials such as feldspar, clay (such as kaolin) and quartz. The main components are silicon, aluminum and oxygen, which account for 90% of the total elements in the earth's crust. Among them, ordinary ceramics are sintered from natural raw materials, with abundant sources, low costs and mature processes. According to performance characteristics and uses, they can be divided into daily ceramics, building ceramics, electrical insulation ceramics, chemical ceramics, etc. Special ceramics are made of high-purity artificially synthesized raw materials, formed and sintered using precision control processes, and have certain special properties to meet various needs. According to their main components, there are oxide ceramics (such as alumina ceramics), nitride ceramics (such as silicon nitride ceramics), carbide ceramics (such as silicon carbide ceramics), metal ceramics, etc. According to different uses, special ceramic materials can be divided into structural ceramics, tool ceramics, and functional ceramics.

[0003] As a new type of material, ceramic materials are widely used in nuclear power, chemical industry, biology, metallurgy and other fields. In the process of processing and transportation of ceramic materials, defects and scratches are inevitable. In actual use, due to its intrinsic brittleness, once cracks occur inside, they will soon expand rapidly due to the test load, causing material failure, which will cause great harm to people's safety and national economic development. Therefore, how to better and faster measure the fracture toughness of ceramic materials, design ceramic materials in a more reasonable way and use them in suitable industrial environments is one of the important issues facing the current industry.

[0004] In fact, there are many methods for measuring the fracture toughness of ceramic materials, including the indentation method: using an indenter to apply pressure on the ceramic surface to produce cracks, and then calculating the fracture toughness based on the length, shape and direction of the cracks; the notched beam method: making an incision in the middle or edge of the ceramic, and then applying a bending force to produce a crack at the incision, and calculating the fracture toughness based on the length and stress intensity factor of the crack; the pre-cracked beam method: making a crack in the middle or edge of the ceramic beam in advance, and then applying a bending force to extend the crack, and calculating the fracture toughness based on the length and stress intensity factor of the crack. These methods require mechanical loading and measuring the force-displacement curve, and measuring the force-displacement curve requires the coordinated action of multiple sensors, and the fixture that clamps the material to be tested needs to be clamped in a suitable position. The high hardness of the fixture causes deformation of the material, which makes the fracture toughness test of the material time-consuming and labor-intensive, and the experimental data is highly dispersed. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention aims to provide a method and device for measuring the fracture toughness of ceramic materials based on laser thermal crack extension. The present invention is based on the laser thermal expansion effect, utilizes the Griffith energy release concept, Griffith fracture criterion, and the relationship between stress intensity factor and energy release rate, obtains a formula suitable for describing the fracture process of ceramic materials under thermal-mechanical coupling, and establishes a method for measuring its fracture toughness.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The fracture toughness measurement method of brittle materials based on laser thermal crack growth includes:

[0008] The tested sample has a crack penetrating the plate surface. Laser probes and thermal imagers are installed on both sides of the ends of the cracks on the tested sample. The laser beam is perpendicular to the plate surface and converges 1.5 mm behind the crack tip.

[0009] Use the laser to inject energy of magnitude W into the crack end, read the temperature change ΔT(x,y) on the plate surface on the thermal imager, and record it in the computer;

[0010] The energy release rate G of the material is obtained by using the energy W, temperature change ΔT(x,y) and crack length change Δa, and Griffith energy release theory;

[0011] The fracture toughness K of the material is determined based on the relationship between the energy release rate and the fracture toughness.

[0012] A further improvement of the present invention is that the tested sample has a crack penetrating the plate surface, and the crack surface is perpendicular to the material surface.

[0013] A further improvement of the present invention is that a three-dimensional right-handed rectangular coordinate system is established with the plate surface as a plane, the crack tip on the tested sample as the origin, the crack extension direction as the x-axis, the axis perpendicular to the crack direction as the y-axis, and the axis perpendicular to the plate surface as the z-axis. The laser action point is 1.5 mm inside the crack tip, and the specific coordinates are (-1.5, 0, 0);

[0014] Through the energy formula, using Griffith's energy balance theory and the basic laws of elastic mechanics, it is obtained that the ratio of crack extension energy to the total laser injection energy is a constant;

[0015] The required formula is as follows:

[0016]

[0017] dQ=cdmΔT=cρ(T-T0)dV

[0018] In the formula: ∈_ij^e represents elastic strain; ∈_ij^T represents thermal strain; α is the thermal expansion coefficient; W is the strain energy; Q is the heat absorbed by the material; E is the elastic modulus; c is the specific heat capacity; ρ is the density.

[0019] A further improvement of the present invention is that the ratio of crack extension energy to laser injection energy is calculated by the following formula:

[0020]

[0021] Where: α is the coefficient of thermal expansion; W is the strain energy; Q is the heat absorbed by the material; E is the elastic modulus; c is the specific heat capacity; ρ is the density.

[0022] A further improvement of the present invention is that the position of the crack on the tested sample is known, the crack on the tested sample is a crack that penetrates the flat plate and the crack surface is perpendicular to the surface of the flat plate.

[0023] A further improvement of the present invention is that the diameter of the laser action point is 0.1 mm, the laser action power is 100 W, and the laser action time is 0.1 s.

[0024] A further improvement of the present invention is that the thickness of the material to be measured is 0.5 mm.

[0025] A fracture toughness measuring device for brittle materials based on laser thermal crack growth, comprising a carbon dioxide laser, a reflector, a convex lens, a camera, a thermal imager and a data processing computer;

[0026] The laser emitted by the carbon dioxide laser adjusts the optical path through a reflector and arrives just above the test piece. It is converged by a convex lens and acts on the surface of the material 1.5 mm behind the crack tip. The thermal imager records the change of the surface temperature distribution of the test piece over time, and the camera records the process of crack expansion and the final length of the crack. The data processing computer calculates the crack area using the crack length and the thickness of the test sample, and calculates the energy used for crack expansion using the energy proportional formula.

[0027] A further improvement of the present invention is that the carbon dioxide laser adopts a 150W carbon dioxide laser.

[0028] A further improvement of the present invention is that the energy ratio calculation formula is as follows:

[0029]

[0030] dQ=cdmΔT=cρ(T-T0)dV (5)

[0031] Where:

[0032] ∈_ij^e represents elastic strain;

[0033] ∈_ij^T represents thermal strain;

[0034] α is the coefficient of thermal expansion;

[0035] W is strain energy;

[0036] E is the elastic modulus;

[0037] Q is the heat absorbed by the material;

[0038] c is the specific heat capacity;

[0039] ρ is the density;

[0040] The energy ratio formula is calculated as follows:

[0041]

[0042] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0043] The present invention provides a method and device for measuring the fracture toughness of brittle materials based on laser thermal expansion. A certain external energy source is introduced to generate thermal expansion inside the material, and the surface changes are measured by simple detection means. According to the derived formula, the energy is converted into the energy to drive crack extension, and then the fracture energy is calculated using the classical Griffith theory, and the fracture toughness is further obtained. The measuring method has simple equipment and is easy to operate. The formula it relies on is widely recognized in the industry, and it has good versatility and strong reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 It is a schematic diagram of crack propagation in the fracture toughness measurement of brittle materials based on laser thermal expansion according to the present invention.

[0046] in, Figure 1 (a) is a schematic diagram before laser irradiation. The blue part is the laser. A crack is prefabricated on the plate sample. The red dot is the point where the laser will act. Figure 1 (b) is a schematic diagram after laser irradiation. The added transparent cone represents the converged laser beam. When irradiated at the red position, the crack extends to a length of Δa.

[0047] Figure 2 It is a schematic diagram of the arrangement of the laser, the measuring device and the tested sample of the present invention.

[0048] Figure 3 is a rendering of an embodiment of the present invention, wherein Figure 3 (a) before laser action, Figure 3 (b) After laser action.

[0049] Description of reference numerals:

[0050] 1-CO2 laser, 2-reflector, 3-computer, 4-thermal imager, 5-convex lens 5, 6-camera, 7-ceramic plate sample, 8-test bench. DETAILED DESCRIPTION

[0051] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0052] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0053] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, the singular forms "a", "an" and "the" are intended to include plural forms unless the context clearly indicates otherwise.

[0054] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0055] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.

[0056] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0057] Example 1

[0058] The present invention provides a method for measuring the fracture toughness of brittle materials based on laser thermal crack extension. The laser radiation energy is input into the end of the material crack by a non-contact energy input method. The material absorbs the laser energy and converts it into thermal energy. The material expands due to the heat and drives the crack to extend forward, thereby achieving the purpose of injecting fracture energy. The fracture toughness of the material is calculated according to the length of the crack extension and the amount of input energy. The method includes the following steps:

[0059] The tested sample has a crack penetrating the plate surface. Laser probes and thermal imagers are installed on both sides of the ends of the cracks on the tested sample. The laser beam is perpendicular to the plate surface and converges at about 1.5 mm behind the crack tip.

[0060] Use the laser to inject energy of magnitude W into the crack end, read the temperature change ΔT(x,y) on the plate surface on the thermal imager, and record it in the computer;

[0061] The energy release rate G of the material is calculated using the energy W, temperature change ΔT(x,y), and crack length change Δa using the Griffith energy release theory.

[0062] The fracture toughness K of the material is determined based on the relationship between the energy release rate and the fracture toughness.

[0063] In this embodiment, the crack on the tested sample penetrates the material surface, and the crack surface is perpendicular to the material surface;

[0064] In this embodiment, a three-dimensional right-handed rectangular coordinate system is established with the plate surface as a plane, the crack tip on the test sample as the origin, the crack extension direction as the x-axis, the Y-axis perpendicular to the crack direction, and the Z-axis perpendicular to the plate surface. The laser action point is about 1.5 mm inside the crack tip, and the specific coordinates are (-1.5, 0, 0).

[0065] Through the energy formula, using Griffith's energy balance theory and the basic laws of elastic mechanics, it is obtained that the ratio of crack extension energy to the total laser injection energy is a constant;

[0066] The required formula is as follows:

[0067]

[0068] dQ=cdmΔT=cρ(T-T0)dV

[0069] In the formula: ∈_ij^e represents elastic strain; ∈_ij^T represents thermal strain; α is the thermal expansion coefficient; W is the strain energy; Q is the heat absorbed by the material; E is the elastic modulus; c is the specific heat capacity; ρ is the density.

[0070] In this embodiment, the ratio of crack extension energy to laser injection energy is calculated by the following formula:

[0071]

[0072] Where: α is the coefficient of thermal expansion; W is the strain energy; Q is the heat absorbed by the material; E is the elastic modulus; c is the specific heat capacity; ρ is the density.

[0073] In this embodiment, the position of the crack on the tested sample is known, the crack on the tested sample is a crack that penetrates the flat plate and the crack surface is perpendicular to the surface of the flat plate.

[0074] In this embodiment, the diameter of the laser action point is 0.1 mm, the laser action power is 100 W, and the laser action time is 0.1 s.

[0075] In this embodiment, the thickness of the material to be measured is 0.5 mm.

[0076] In this embodiment, the fracture toughness of brittle materials is measured by a measuring device such as a laser.

[0077] In this embodiment, the fracture toughness measuring device includes a camera, a thermal imager and a data processing computer.

[0078] Example 2

[0079] See also Figure 1-2 The present invention discloses a method for measuring fracture toughness of brittle materials based on laser thermal expansion, and involves a test sample, a laser and a measuring device group.

[0080] The laser and measuring device group includes a 150W carbon dioxide laser 1, a reflector 2, a convex lens 5, a thermal imager 4 for detecting the temperature field, a camera 6 for recording the crack extension, a computer 3 for controlling the laser and collecting experimental data, a test bench 8, and a ceramic plate sample 7. The laser emitted by the carbon dioxide laser adjusts the optical path through the reflector and arrives directly above the experimental piece, and after being converged by the convex lens, acts on the rear edge of the crack tip on the surface of the material at about 1.5 mm; the thermal imager records the change of the surface temperature distribution of the experimental piece over time, and the camera records the process of crack extension and the final length of the crack.

[0081] Among them, the carbon dioxide laser is a gas laser that uses CO2 gas as the working substance. Its working principle is based on the electron energy level transition causing molecular vibration and rotation. The specific process is as follows:

[0082] Gas mixture: The interior of the laser is filled with a mixture of CO2, nitrogen, and helium, with CO2 being the primary laser-producing substance.

[0083] Lamp pump: Use high voltage current to pass through a gas mixture, thereby exciting the gas to a high energy state, producing ionization and discharge process.

[0084] Energy level transition: During the discharge process, the electrons of the CO2 molecule are excited to a high energy level and then quickly transition back to a lower energy level. During the transition, it releases energy and causes the molecule to vibrate and rotate.

[0085] Resonant feedback: These vibrations and rotations cause the laser energy levels in the CO2 molecule to resonate with the energy levels in the other two gases, causing the CO2 molecule to emit a laser beam of a specific wavelength.

[0086] Beam amplification and output: The beam repeatedly shuttles between convex mirrors, is amplified, and finally transmitted through a reflector.

[0087] The main features of CO2 lasers are:

[0088] High power output: CO2 lasers are capable of producing high-power laser beams. The laser power produced in a continuous mode can reach over 20 kilowatts, and the pulsed mode is equally powerful.

[0089] Specific wavelength: The wavelength of the laser it emits is 10.6 microns, which is in the infrared region and cannot be detected by the naked eye.

[0090] Efficient conversion: As a commercial model, the conversion efficiency of carbon dioxide lasers can reach 10%. The electro-optical conversion efficiency of some products can generally reach 15% to 25%, and the highest can even reach 30% to 40%, which exceeds other gas lasers.

[0091] Good beam quality: The output beam has the advantages of high optical quality, good coherence, narrow linewidth, and stable operation.

[0092] The basic principle of thermal imaging is to use infrared radiation generated by the surface of an object, the intensity of which is proportional to the temperature of the object. The sensor captures this infrared radiation and converts it into digital signals, which are processed to generate thermal images. These images represent different temperature areas with different colors or brightness, thereby intuitively showing the temperature distribution on the surface of the target object.

[0093] The main features of thermal imagers are:

[0094] Non-contact temperature measurement: Thermal imagers can measure temperature without touching the target object, avoiding the errors and interference that may be caused by traditional temperature measurement methods.

[0095] High-precision temperature measurement: Through advanced sensors and image processing technology, thermal imagers can achieve high-precision temperature measurement to meet the needs of various application scenarios.

[0096] Real-time monitoring: Thermal imagers can monitor the temperature distribution on the surface of target objects in real time, providing timely and accurate information for fault diagnosis, safety protection, etc.

[0097] Visual output: The thermal images generated by the thermal imager are intuitive and easy to understand, making it convenient for users to analyze, record and export.

[0098] Ceramic plate samples are samples prepared for testing the performance and quality of ceramic plates or for scientific research. Common ceramic plate materials include inorganic non-metallic materials such as alumina, zirconia, and kaolin clay. Ceramic plates of different materials have different physical and chemical properties, such as weather resistance, impact resistance, and chemical corrosion resistance.

[0099] The crack area is calculated using the crack length and the thickness of the sample being tested, and the energy used for crack growth is calculated using the energy proportional formula.

[0100] The energy ratio calculation formula is as follows:

[0101]

[0102] dQ=cdmΔT=cρ(T-T0)dV (5)

[0103] Where:

[0104] ∈_ij^e represents elastic strain;

[0105] ∈_ij^T represents thermal strain;

[0106] α is the coefficient of thermal expansion;

[0107] W is strain energy;

[0108] E is the elastic modulus;

[0109] Q is the heat absorbed by the material;

[0110] c is the specific heat capacity;

[0111] ρ is the density;

[0112] The energy ratio formula is calculated as follows:

[0113]

[0114] Example 3

[0115] The steps of using the method for measuring fracture toughness of brittle materials based on laser thermal expansion of the present invention are as follows:

[0116] Step 1: Prepare a brittle material ceramic plate with a prefabricated crack, and the crack length on the test sample is a;

[0117] Step 2: Place the test sample on the test bench and fix it, and adjust the laser position so that the laser action point is about 1.5 mm behind the crack tip on the test sample;

[0118] Step 3: Place the thermal imager and camera so that their detection range can cover the entire sample surface, and measure the change of temperature distribution on the sample surface over time and the crack extension;

[0119] Step 4: Determine the energy ratio of the total laser injection energy as a constant value through formulas (1)-(5), and use energy ratio calculation formula (6) combined with simulation analysis to calculate the ratio of energy used for crack propagation to the total laser injection energy;

[0120] Step 5: Calculate the crack surface area and calculate the material fracture toughness based on the energy obtained for expansion.

[0121] Example 4

[0122] like Figure 3 As shown, for yttrium stabilized zirconia, a sample with a length of 50 mm, a width of 50 mm, and a thickness of 0.5 mm was selected for testing, and the results were as follows:

[0123] Table 1 Laser irradiation time and calculated fracture toughness

[0124]

[0125] The fracture toughness measurement value given in the reference Preparation and Mechanical Properties of Zirconia Ceramics Doped with Different Y2O3 Contents is 13Mpa*m -0.5 , it can be found that this method is very accurate in calculating the fracture toughness of brittle materials.

[0126] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0127] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The above content is only to illustrate the technical idea of ​​the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for measuring fracture toughness of brittle materials based on laser thermal crack growth, characterized in that: include: The tested sample has a crack penetrating the plate surface. Laser probes and thermal imagers are installed on both sides of the ends of the cracks on the tested sample. The laser beam is perpendicular to the plate surface and converges 1.5 mm behind the crack tip. Use the laser to inject energy of magnitude W into the crack end, read the temperature change ΔT(x,y) on the plate surface on the thermal imager, and record it in the computer; The energy release rate G of the material is obtained by using the energy W, temperature change ΔT(x,y) and crack length change Δa, and Griffith energy release theory; The fracture toughness K of the material is determined based on the relationship between the energy release rate and the fracture toughness.

2. The method for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 1, characterized in that: The tested specimen has a crack penetrating the plate surface, and the crack plane is perpendicular to the material surface.

3. The method for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 1, characterized in that: Take the plate surface as the plane, the crack tip on the tested sample as the origin, the crack extension direction as the x-axis, the perpendicular to the crack direction as the y-axis, and the perpendicular to the plate surface as the z-axis. Establish a three-dimensional right-handed rectangular coordinate system. The laser action point is 1.5 mm inside the crack tip, and the specific coordinates are (-1.5, 0, 0). Through the energy formula, using Griffith's energy balance theory and the basic laws of elastic mechanics, it is obtained that the ratio of crack extension energy to the total laser injection energy is a constant; The required formula is as follows: dQ=cdmΔT=cρ(T-T0)dV In the formula: ∈_ij^e represents elastic strain; ∈_ij^T represents thermal strain; α is the thermal expansion coefficient; W is the strain energy; Q is the heat absorbed by the material; E is the elastic modulus; c is the specific heat capacity; ρ is the density.

4. The method for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 3, characterized in that: The ratio of crack extension energy to laser injection energy is calculated by the following formula: Where: α is the coefficient of thermal expansion; W is the strain energy; Q is the heat absorbed by the material; E is the elastic modulus; c is the specific heat capacity; ρ is the density.

5. The method for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 1, characterized in that: The position of the crack on the tested sample is known, the crack on the tested sample is a crack that penetrates the plate and the crack surface is perpendicular to the surface of the plate.

6. The method for measuring fracture toughness of brittle materials based on laser thermal crack growth according to claim 1, characterized in that: The diameter of the laser action point is 0.1mm, the laser action power is 100W, and the laser action time is 0.1s.

7. The method for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 1, characterized in that: The thickness of the material being tested is 0.5 mm.

8. A device for measuring fracture toughness of brittle materials based on laser thermal crack propagation, characterized in that: It includes a CO2 laser, a reflector, a convex lens, a camera, a thermal imager and a data processing computer; The laser emitted by the CO2 laser adjusts the optical path through a reflector and reaches directly above the test piece. After being converged by a convex lens, it acts on the surface of the material 1.5 mm behind the crack tip. The thermal imager records the change of the surface temperature distribution of the test piece over time, and the camera records the process of crack expansion and the final length of the crack. The data processing computer calculates the crack area using the crack length and the thickness of the sample being tested, and calculates the energy used for crack growth using the energy proportional formula.

9. The device for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 8, characterized in that: The CO2 laser uses a 150W CO2 laser.

10. The device for measuring fracture toughness of brittle materials based on laser thermal crack propagation according to claim 8, characterized in that: The energy ratio calculation formula is as follows: dQ=cdmΔT=cρ(T-T0)dV (5) Where: ∈_ij^e represents elastic strain; ∈_ij^T represents thermal strain; α is the coefficient of thermal expansion; W is strain energy; E is the elastic modulus; Q is the heat absorbed by the material; c is the specific heat capacity; ρ is the density; The energy ratio formula is calculated as follows:

Citation Information

Patent Citations

  • Thermotropic liquid crystal polymer toughening epoxy resin and its preparation method

    CN1083497A

  • Measuring method for fracture toughness of bubbling interface of bridge deck pavement layer

    CN108519276A

  • Method for estimating plane strain breaking tenacity KIC of high-strength steel

    CN108956266A

  • Non-alkali aluminium silicate glass as well as preparation method and application thereof

    CN109231819A

  • Method for accurately measuring elastic modulus of tunnel rock in cold region after repeated freeze-thaw damage

    CN109283086A